PENERAPAN WEB SERVICES DAN ALGORITMA GENETIKA UNTUK MENAMPILKAN JADWAL UJIAN TUGAS AKHIR STUDI KASUS : JURUSAN TEKNIK INFORMATIKA UNIVERSITAS HALU OLEO - Waode Nur Lailah; L.M Fid Aksara; Natalis Ransi (semanTIK, 2018)
The role of web service is needed as a medium for sharing data and inter-process functionality so that an application can connect with other applications without depending on the programming language or operating system. By using the web service Final Project exam schedule is not only known by students who will do the trial examination but can also be known by all students where the exam schedule will be sent to the web service provider then the web service engine will work to display the exam schedule on several websites that have been provided and by using genetic algorithms direct exam schedules can be determined automatically. This is where the role of web service is in carrying out the data exchange process. In this study, the technology that will be used is SOAP (Simple Object Access Protocol) because SOAP is a standardized protocol by W3C (World Wide Web Consortium), besides that it is also used Genetic Algorithm to automatically set exam schedules.The results obtained in this study that the application of web services can run well. Success can be seen from the results of testing the system where the exam schedule The final task can appear on several different websites and can change the data that is on the system that runs without entering into the system.Keywords - Web Service, SOAP, Genetic Algorithm DOI: 10.5281/zenodo.1471102